2005
DOI: 10.1021/es051803v
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Concentrations of Polycyclic Aromatic Hydrocarbons in Burnt Woodland Soils

Abstract: Little is known of the fate of polycyclic aromatic hydrocarbons (PAHs) in soils under burnt woodland. It is not clear what the behavior of the overlying wood ash layer will be along months. In this study, the levels of eight representative PAHs in the 1-5 cm layer of a periurban woodland soil that had undergone wildfire were compared with those measured in nearby and distant unburnt periurban woodland soils and in a distant unburnt rural woodland soil, and the levels at the burnt site were monitored during som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 28 publications
4
60
2
Order By: Relevance
“…Although a peak in their concentration was observed in the soil heated at 200ºC, in coincidence with the peak for phytotoxicity, the concentrations found were too low (under 1 mg kg -1 in all cases) to be the cause of phytotoxicity, since phytotoxic effects of PAHs have only been reported in soil concentrations ranging from 25 to >100 mg kg -1 (Efroymson et al, 1997). Besides, the PAHs concentrations found here are similar to values found by other authors in woodland burnt soils in Spain (García-Falcón et al, 2006), so it cannot be said that…”
Section: Soil Properties T (ºCsupporting
confidence: 69%
See 1 more Smart Citation
“…Although a peak in their concentration was observed in the soil heated at 200ºC, in coincidence with the peak for phytotoxicity, the concentrations found were too low (under 1 mg kg -1 in all cases) to be the cause of phytotoxicity, since phytotoxic effects of PAHs have only been reported in soil concentrations ranging from 25 to >100 mg kg -1 (Efroymson et al, 1997). Besides, the PAHs concentrations found here are similar to values found by other authors in woodland burnt soils in Spain (García-Falcón et al, 2006), so it cannot be said that…”
Section: Soil Properties T (ºCsupporting
confidence: 69%
“…As several authors have indicated the apparition of aromatic compounds in soil during forest fires (García-Falcón et al, 2006), the presence of polycyclic aromatic hydrocarbons (PAHs) was also determined, in order to test if they may be responsible for phytotoxicity.…”
Section: Soil Heating Experimentsmentioning
confidence: 99%
“…Simpson et al (1996) noted that the relationship between total PAHs and organic carbon is significant only for highly contaminated sites where the total PAH concentration was in excess of 2,000 μg/kg, and the high concentration had only occurred in the 2-5 cm layer of the HU4 section in the study area Besides the SOC, ionic strength , pH (Laor et al 1998), and colloids can also influence the binding of PAHs in soils. The PAHs downward transportation may have been assisted by increased mobilization of PAHs associated with dissolvable organic matter due to an increase in soil pH (Gabcia-Falcón et al 2006). This view is supported by the fact that pH values increase from 4 to 5 with depth.…”
Section: Variations Of Individual Pahs Within Vertical Sectionsmentioning
confidence: 93%
“…Determination of PAHs in different media has been extensively reported in the literature (García-Falcón et al, 2004a, b;Rey-Salgueiro et al, 2004;García-Falcón et al, 2005;García-Falcón et al, 2006). The quantity of PAHs adsorbed was determined by difference between the initial Sorption kinetics of PAHs to HSs were monitored to know whether the time necessary for equilibrium or constant sorption could be lower than 24 h. Kinetics were measured by duplicate in water at a low (58 mg L -1 ) and a high (464 mg L -1 ) concentration of HSs.…”
Section: Methodsmentioning
confidence: 99%